2011
DOI: 10.1371/journal.pone.0020299
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Proliferation by an Anti-EGFR Aptamer

Abstract: Aptamers continue to receive interest as potential therapeutic agents for the treatment of diseases, including cancer. In order to determine whether aptamers might eventually prove to be as useful as other clinical biopolymers, such as antibodies, we selected aptamers against an important clinical target, human epidermal growth factor receptor (hEGFR). The initial selection yielded only a single clone that could bind to hEGFR, but further mutation and optimization yielded a family of tight-binding aptamers. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 49 publications
0
132
1
2
Order By: Relevance
“…36 As seen in Figure 3G, SurR9-C84A exhibited proliferation inhibition in undifferentiated PCNA was expressed at the G 2 /M phase of the cell cycle, while Ki67 was expressed at all active phases of cell division except at the resting phase (G 0 ). 37 Therefore, these are both excellent markers for determining proliferation in differentiated SK-N-SH cells.…”
Section: Cell-proliferation Studymentioning
confidence: 80%
“…36 As seen in Figure 3G, SurR9-C84A exhibited proliferation inhibition in undifferentiated PCNA was expressed at the G 2 /M phase of the cell cycle, while Ki67 was expressed at all active phases of cell division except at the resting phase (G 0 ). 37 Therefore, these are both excellent markers for determining proliferation in differentiated SK-N-SH cells.…”
Section: Cell-proliferation Studymentioning
confidence: 80%
“…Recently, our lab and others have generated aptamers that recognize a limited number of other cell surface receptors (Dollins et al, 2008a;Li et al, 2011) and have demonstrated that such aptamers can be internalized into cells and carry cargoes into them. Therefore this approach holds much promise for therapeutic development but unfortunately its utility is still hindered by significant limitations (Dollins et al, 2008b;Tiemann and Rossi, 2009;Zhou and Rossi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several anti-ErbB-specific aptamers have been developed (10)(11)(12)(13)(14). They generally show high affinity and specificity to their targets and, in the case of ErbB-1-and ErbB-3-specific aptamers, they also inhibit the proliferation of cultured cancer cells (10,14). Notably, an aptamer against ErbB-1/EGFR was able to inhibit tumor growth in a mouse model (12), and ErbB-2-specific aptamers were used to deliver siRNAs targeting B-cell lymphoma 2 (Bcl-2) (15).…”
mentioning
confidence: 99%